Timeline-Based Space Operations Scheduling with External Constraints - Chien, Steve; Tran, Daniel; Rabideau, Gregg; Schaffer, Steve; Mandl, Daniel; Frye, Stuart (Proceedings of the International Conference on Automated Planning and Scheduling, 2010)
We describe a timeline-based scheduling algorithm developed for mission operations of the EO-1 earth observing satellite. We first describe the range of operational constraints for operations focusing on maneuver and thermal constraints that cannot be modeled in typical planner/schedulers. We then describe a greedy heuristic scheduling algorithm and compare its performance to both the prior scheduling algorithm - documenting an over 50% increase in scenes scheduled with estimated value of millions of dollars US. We also compare to a relaxed optimal scheduler showing that the greedy scheduler produces schedules with scene count within 15% of an upper bound on optimal schedules.